The effect of housing system on rabbit growth performance, carcass traits, and meat quality characteristics of different muscles. (November 2022) - Krunt, Ondřej; Zita, Lukáš; Kraus, Adam; Bureš, Daniel; Needham, Tersia; Volek, Zdeněk
Abstract: The present study analysed the effect of housing system (caged versus penned) on the growth performance, carcass traits, and meat quality of rabbits. The physiochemical quality of five muscles was evaluated, together with the chemical composition and fatty acid profile of the meat from the hind leg. Sensory properties of the longissimus lumborum (LL) was also assessed. The LL yields were higher in caged rabbits. According to the results, meat from rabbits raised in cages had higher b* values for the LL (i.e., meat was yellower) than rabbits raised in pens. In addition, the quadriceps femoris from penned rabbits had higher a* and b* values (i.e., were redder and yellower) than caged rabbits. The MUFAs (18:1 n-9 and 20:1 n-9) and ash contents of the hind leg meat were higher in caged rabbits. In conclusion, while housing system influenced the physiochemical traits of rabbit meat, the sensory properties were not influenced. Highlights: Conventional cages and alternative pens rabbits housing systems were compared. Quadriceps femoris had higher a*b* values in penned than in caged rabbits. Total MUFAs were higher in caged than in penned rabbits. Peroxidability index was higher in pen-housed than in cage-housed rabbits. Rabbits in cages had greater Longissimus lumborum yields than those in pens.